Development of gas detection and database system on cupping practice - Renuga, Subarmaniam (2022)
Cupping Therapy is a technique that involves the use of cupping glasses to smooth the blood's journey in the body. The cupping procedure requires the use of a cup and a suction device to remove air from the cup, resulting in a negative pressure inside the cup that attracts the skin and subcutaneous tissue. Dry and wet cupping are the two main types of cupping. A device that detects the presence or concentration of a gas in the atmosphere is known as a "gas sensor." This sensor produces an appropriate potential difference based on the gas concentration by changing the resistance of the material inside the sensor, which can be detected as the output voltage. During the cupping process, the cup attached to the patient's body will act as a vacuum that will inhale the oxygen inside the cup. In the process of inhalation, a gas will be produced in the cup. However, the gas produced in the cup has the potential to be dangerous for medical practitioners during therapy sessions. Moreover, monitoring of the gas released from the cup can be used to indicate the patient's level of health. A database system should be developed to keep a record of a patient's health status. The main objectives of this project are to develop a gas detection mechanism, a cupping gas database system, and finally test the dry and wet cupping systems. First, the healthcare practitioner will enter the patient's details into the system After that, the system will read the input. If not, the system will read the patient information again, and if so, the system will send the data to the database. The hardware consists of a "gas chamber" that traps gas during the cupping process and four Sensors used are MQ7 (Carbon Monoxide Gas Sensor), MQ5 (Carbon Dioxide Gas Sensor), MQ135 (Ammonia Gas Sensor) and MQ13 l (Nitric Oxide Gas Sensor) placed in the gas chamber. Before starting sensor reading, a GUI (Guided User Interface) was developed. The GUI will be programmed using Visual Code Studio by using Phyton codes. All patient data will be stored in a database, which is PhpMyAdmin as I-Cloud. The Arduino Uno Wi-Fi microcontroller is used to convey information to the sensors, namely the MQ5, MQ7, MQ135 and MQ131. For all the sensor reading data, must be developed into an application, namely BLYNK. It's an app to show and send the sensor reading to GUI (Guided User Interface). For the simulation of the mechanism, the programme used is AUTOCAD. The results obtained will be investigated and discussed in this thesis.